2012
DOI: 10.1016/j.jcat.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of benzene by methanol: Single-site kinetics over H-ZSM-5 and H-beta zeolite catalysts

Abstract: Benzene methylation by methanol is studied on acidic zeolites H-ZSM-5 (MFI) and H-beta (BEA) to investigate the influence of the catalyst topology on the reaction rate. Experimental kinetic measurements at 350 °C using extremely high feed rates to suppress side reactions show that methylation occurs considerably faster on H-ZSM-5 than on H-beta. Theoretical rate constants, obtained from first-principles simulations on extended zeolite clusters, reproduce a higher methylation rate on H-ZSM-5 and provide additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 45 publications
18
130
0
Order By: Relevance
“…The role of catalyst topology has also extensively been studied for methylation reactions of alkenes and aromatics. 28,35,36,65 An optimal fit of the guest molecules in the zeolite pores seemed to be a determining factor for the reaction kinetics. 56 Next to reactivity, the catalyst topology and acidity were also found to impact diffusion rates of reaction products.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The role of catalyst topology has also extensively been studied for methylation reactions of alkenes and aromatics. 28,35,36,65 An optimal fit of the guest molecules in the zeolite pores seemed to be a determining factor for the reaction kinetics. 56 Next to reactivity, the catalyst topology and acidity were also found to impact diffusion rates of reaction products.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Space -and time resolved spectroscopic techniques are nowadays able to image single particles and molecules 9,10,27 and kinetic measurements can yield information on isolated reaction steps. 28,29 Such kinetic information can at later instance be introduced in a micro-kinetic model to study the steadystate behavior of the process. [30][31][32][33] Also from a theoretical perspective many efforts to obtain profound understanding of the chemistry behind the MTH process have been performed and we refer the reader to some interesting reviews on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Consequently, numerous studies focused on the methylation by methanol, dimethyl ether or methoxides of aromatics and alkenes in the framework of the MTO process. [16,17,26,42,44,46,82,83] It should be mentioned that the static approach with finite cluster models as applied in most of these studies has been very successful in reproducing and predicting experimentally measured kinetic data. [16,17] However, a similar approach is not applicable for the study of methylation reactions in the large pore AFI structured H-SSZ-24 as will be demonstrated in this case study.…”
Section: Case Study Ii: Simulating Competing Pathways For Benzene Metmentioning
confidence: 99%
“…Similar observations were reported earlier for the methylation of benzene in H-ZSM-5 and H-Beta. [17] Step 1 (R-IM) 138.5 43.6…”
Section: Case Study Ii: Simulating Competing Pathways For Benzene Metmentioning
confidence: 99%
See 1 more Smart Citation